JAWARA DALAM PUSARAN POLITIK: KOOPTASI POLITIK ORGANISASI TTKKDH (TJIMANDE TARI KOLOT KEBON DJERUK HILIR) - Nabela, Fransisca; Shihabudin, Rifky; Yadia, Putri Khispa; Dari, Dwi Wulan; Mahpudin, Mahpudin (Universitas Panca Marga, 2024)
ABSTRACT This article examines the relationship between power relations or political co-optation within the cultural arts organization TTKKDH (Tjimande Tari Kolot Kebon Djeruk Hilir) in the politics of the Banten region. Local or traditional culture with martial arts elements in Banten is synonymous with the term Jawara. This explains the direction of TTKKDH as a cultural and martial arts organization that is included in the Jawara path. The closeness of the TTKKDH organization to political elites is in the public spotlight, even the members or leaders of TTKKDH are part of the political elite themselves, with the principle of solidarity and loyalty the TTKKDH organization very easily carries out a pattern of political co-optation because all members must follow the direction of the chairman. Behind the cultural arts of martial arts, TTKKDH aims to obtain state resources in the form of economic interests, so that there can be a reciprocal relationship between the TTKKDH organization and the political elite in the Banten region. In understanding this phenomenon, researchers understand and analyse it using the political theory of co-optation according to Markus Holdo, so this research uses qualitative methods with a phenomenological approach. The results of this research show that there are efforts and strategies of the TTKKDH organization in maintaining, accessing and expanding relationships with political actors. Currently, TTKKDH is using a neutral face in expanding relationships so that it has close ties with several political parties. The political co-optation that occurred within the TTKKDH organization to mobilize the masses from within the organization to assist in legitimizing the victory of political contestation, from this indicates a patron-client pattern carried out by the TTKKDH organization. Keywords: Political Co-optation, Jawara, TTKKDH